2018
DOI: 10.7202/1051695ar
|View full text |Cite
|
Sign up to set email alerts
|

Étude comparative de l’adsorption du colorant Victoria Bleu Basique à partir de solutions aqueuses sur du carton usagé et de la sciure de bois

Abstract: L’adsorption du Victoria Bleu Basique (VBB) sur du carton usagé (CU) a été étudiée et comparée à celle sur de la sciure de bois (SB). Le CU a été caractérisé par différentes techniques analytiques. Les paramètres influençant la réaction ont été déterminés, tels que le pH, le dosage des adsorbants et le temps de contact. L’étude cinétique a révélé que la réaction de surface s’adapte au modèle de pseudo-second ordre et que la diffusion intraparticulaire est une étape déterminante après les premières minutes. L’i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Figure 5 shows that the broadband at 3412.92 cm −1 is related to the elongation vibration of the O-H bond [ 17 ], mainly due to the presence of cellulose molecules [ 18 ]. The peak observed at 2922.93 is attributed to the C-H elongation and bending vibration of the CH 3 methyl group [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 5 shows that the broadband at 3412.92 cm −1 is related to the elongation vibration of the O-H bond [ 17 ], mainly due to the presence of cellulose molecules [ 18 ]. The peak observed at 2922.93 is attributed to the C-H elongation and bending vibration of the CH 3 methyl group [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained show that the equilibrium time is independent of the initial dye concentration and that the amount of dye fixed on the adsorbent increases with the contact time. Figure 8 reveals the existence of two phases during the adsorption of the MB by the SCB: the first one is the fastest taking 5 minutes, which can be explained by the existence of a high affinity between the cations of the dye and the adsorbent [ 17 ], and the second is a slow phase where equilibrium is gradually reached after 20 minutes. This may be due to the saturation of the active sites in the support [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…The study of the adsorption kinetics of salicylic acid demonstrated the values and benefits of its depolluting properties but the choice of the most appropriate kinetic model for this material will facilitate the study and give more reliable results (Adib et al, 2018;Giraldo et al, 2018;Mekhalef et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Thermodynamic parameters such as thermodynamic equilibrium constant K d , Gibbs free energy variation ΔG 0 , enthalpy variation ΔH 0 , and entropy variation ΔS 0 are among the most important parameters involved in the establishment of an adsorption system, thus to evaluate the feasibility and nature of the adsorption process [ 50 ]. The thermodynamic parameters were obtained from the following equations [ 51 ]: where k is the equilibrium constant (L/mg), R is the gas constant (8.314 J/mol.K), and T is the absolute temperature (K).…”
Section: Methodsmentioning
confidence: 99%